Motivation, Engagement, and Performance Dynamics in the Gig Economy: Understanding Real Estate Agents Beyond Formal Employment - Basori, Ahmad (Cv. Syntax Corporation Indonesia, 2025)
The property agent profession in Indonesia falls within the framework of the gig economy, where agents work with high flexibility, informal working relationships, and commission-based income. However, industry data (2024) shows that only 8.2%–17.4% of agents contribute consistently each month, raising questions about the psychological mechanisms that affect their motivation, engagement, and performance. This study aims to understand how agents construct these three aspects and identify the differences between consistent and inconsistent agents in a property partnership system. The research used a qualitative approach through narrative inquiry and thematic analysis, with 12 property agents registered under AREBI East Java as the main participants and triangulation from 2 coordinators, 2 branch managers, and 1 representative of AREBI East Java. The analysis shows that agent motivation is shaped by the interaction of internal and external factors, with internal motivation being the main determinant of sustainable contribution. Engagement appears in three interrelated dimensions—emotional, behavioral, and cognitive—and serves as a connecting mechanism between motivation and performance. Performance in the context of the gig economy is more accurately understood through the consistency of contribution (task performance and contextual performance) than short-term results. This research resulted in a conceptual model that revises the literature on work dynamics outside of formal employment, with managerial implications to improve the consistency of agent contributions through new agent activation programs, engagement support systems, and learning and collaboration programs.